A 3DHZETRN Code in a Spherical Uniform Sphere with Monte Carlo Verification - Wilson, John W.; Slaba, Tony C.; Badavi, Francis F.; Reddell, Brandon D.; Bahadori, Amir A. (My University, 2016)
The computationally efficient HZETRN code has been used in recent trade studies for lunar and Martian exploration and is currently being used in the engineering development of the next generation of space vehicles, habitats, and extra vehicular activity equipment. A new version (3DHZETRN) capable of transporting High charge (Z) and Energy (HZE) and light ions (including neutrons) under space-like boundary conditions with enhanced neutron and light ion propagation is under development. In the present report, new algorithms for light ion and neutron propagation with well-defined convergence criteria in 3D objects is developed and tested against Monte Carlo simulations to verify the solution methodology. The code will be available through the software system, OLTARIS, for shield design and validation and provides a basis for personal computer software capable of space shield analysis and optimization.
Citation: Wilson JW, Slaba TC, Badavi FF, Reddell BD, and Bahadori AA 2014 A 3DHZETRN Code in a Spherical Uniform Sphere with Monte Carlo Verification NASA/TP-2014-218271 NASA Langley Research Center: Hampton, VA http://ntrs.nasa.gov/search.jsp?R=20140006706
Keywords: RADIATION SHIELDING; Monte Carlo Method; Extraterrestrial Radiation; Light Ions; Neutrons; Lunar Exploration